2014
DOI: 10.1136/lupus-2014-000056
|View full text |Cite
|
Sign up to set email alerts
|

Cell-bound complement activation products in systemic lupus erythematosus: comparison with anti-double-stranded DNA and standard complement measurements

Abstract: ObjectiveTo compare the performance characteristics of cell-bound complement (C4d) activation products (CBCAPS) on erythrocyte (EC4d) and B cells (BC4d) with antibodies to double-stranded DNA (anti-dsDNA) and complement C3 and C4 in systemic lupus erythematosus (SLE).MethodsThe study enrolled 794 subjects consisting of 304 SLE and a control group consisting of 285 patients with other rheumatic diseases and 205 normal individuals. Anti-dsDNA and other autoantibodies were measured using solid-phase immunoassays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 22 publications
11
94
0
Order By: Relevance
“…Complement activation results in the formation of complement activation products that bind covalently to blood cells [11, 28, 29]. The performance characteristics of these cell-bound complement activation products (CB-CAPs) have recently been validated in a prospective multicenter clinical study [30] that showed that elevated B lymphocyte complement 4 derived ligand (BC4d) or erythrocyte complement 4 derived ligand (EC4d) have 22% higher sensitivity than low complement for the diagnosis of SLE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complement activation results in the formation of complement activation products that bind covalently to blood cells [11, 28, 29]. The performance characteristics of these cell-bound complement activation products (CB-CAPs) have recently been validated in a prospective multicenter clinical study [30] that showed that elevated B lymphocyte complement 4 derived ligand (BC4d) or erythrocyte complement 4 derived ligand (EC4d) have 22% higher sensitivity than low complement for the diagnosis of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…1 ) [30]. Patients are considered tier 1 positive if titer of specific autoantibodies is above cut-off (anti-dsDNA > 301 units and positivity is confirmed by the Crithidia luciliae immunofluorescence test, or anti-Smith > 10 units), or if CB-CAPs are strongly positive (EC4d > 75 units or BC4d > 200 units).…”
Section: Introductionmentioning
confidence: 99%
“…The performance of an assay panel comprised of cell-bound complement activation products alongside established markers, such as anti-dsDNA, ANA and anti-MCV, demonstrated 86% specificity and 80% sensitivity in distinguishing SLE from other autoimmune rheumatic disease (Kalunian et al, 2012; Putterman et al, 2014). The test proved 33% more specific than ANA-based tests and 48% more sensitive than the anti-dsDNA test.…”
Section: Discussionmentioning
confidence: 99%
“…40 These findings have been confirmed and refined to a commercially available, weighted SLE risk score with a two tier design. 41 …”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%